Toward an analytical criminology: the micro-macro problem, causal mechanisms, and public policy - Matsueda, Ross L. (Criminology, 2017)
In this address, I revisit the micro–macro problem in criminology, arguing for an “analytical criminology” that takes an integrated approach to the micro–macro problem. I begin by contrasting an integrated methodological-individualist approach with traditional holist and individualist approaches. An integrated approach considers the concept of emergence and tackles the difficult problem of specifying causal mechanisms by which interactions among individuals produce social organizational outcomes. After presenting a few examples of micro–macro transitions relevant to criminology, I discuss research programs in sociology and economics that focus on these issues. I then discuss the implications of social interaction effects for making causal inferences about crime and for making crime policy recommendations.